Women’s feltibnkhafaja - Fares, Issa; al karemkdr, Rami (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Many sources have urged IbnKhafajah to be so keen on woman, which had so clear impact on his soul, and this has led him to experience love in a distinctive manner. Those factors have overlapped with each other to form an integrated fabric, Which has been overwhelmed by the poet’s passionate soul against the harbingers external reality. He hasn’t left his surroundings to escape the deteriorated political and social conditions. However, he turned toward the depth of his soul, rebelling against those conditions and refusing them. Throughout his artistic pictures, he has drawn his relation with woman taking from nature his own distinctive psychological view. Therefore, woman becomes a sensory and merely concept at the same time. He has started to gift it the most sincere and hottest emotions. So, it has been crucial to realise the factors that which have shaped the motives of his own experience with woman and problematic of her existence in in his poetry and his life. IbnKhafajah’s flirtatious experience and his relation with woman are to with factors connected with political and social conditions that have distinguished his era, and others; inner, related to his distinctive personality. These factors have helped to shape this experience for the poet and develop and matur it.